PENGARUH LINGKUNGAN KERJA, KOMPENSASI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN DI RS â€œXâ€ - Handaru, Agung Wahyu; Utomo, Try; R Sudiarditha, I Ketut (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2013)
The purposes of the research are: 1) to get some information related with work environment, compensation, organizational commitment and employeeâ€™s job satisfaction at Hospital â€œXâ€, 2) to test the influence of work environment towards employee Job satisfaction, 3) to test the influence of compensation policy towards employee Job satisfaction, 4) to test the influence of organizational commitment towards employee Job satisfaction, 5) to test the influence of work environment, compensation and organizational commitment towards employee Job satisfaction. The analysis implemented in this research was descriptive and explanatory analysis. The samples in this research are 120 grade III employees in Hospital â€œXâ€. The result showed that the work environment, compensation policy and organizational commitment have a positive and significant impact toward Job satisfaction. Keywords: Work environment, Compensation, Organizational Commitment and Job Satisfaction